TRAFFIC CALMING PROBLEMS IN NEIGHBOURHOODS (Perner's Contacts, 2011)
The article deals actual problems which result from project of traffic calming area.There are three examples of the traffic calming areas. Two of them are examples of“Zone 30” and the next one is the no good example of “Residential Zone”. Thereare shown different curbs, which are used in traffic calming.